Hybrid data regression model based on the generalized adaptive resonance theory neural network - Wong S.Y.; Yap K.S.; Lim C.P.; Lee E.W.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Arts computing; Benchmarking; E-learning; Fire protection; Fires; Learning algorithms; Neural networks; Regression analysis; Resonance; Thermal Engineering; Adaptive resonance theory; Adaptive resonance theory neural networks; Fire safety engineering; Fully online learning; Generalized Regression Neural Network(GRNN); Ordering algorithms; Regression problem; Thermal interfaces; Learning systems